The UTILIZATION OF KELAKAI LEAF SILAGE (Stenochlaena palustris) AS SUPPLEMENTARY FEED FOR KELABAU (Osteochilus melanopleurus) IN BIOFLOC SYSTEM - Syahputri, Octaviana D; Fauzana, Noor A; Hanafie, Agussyarif; Nugroho, Agung (Journal of Aquatropica Asia, 2025)
Kelabau is a species of indigenous fish from Kalimantan and Sumatra that is now rarely found in rivers. This is due to the fishing by fishermen who are less selective for years without being balanced with cultivation efforts. Cultivations have several aspects that need to be considered, namely the availability of feed that contains good nutrients and is in accordance with the needs of fish. Kelakai is an alternative that can be used as additional feed for kelabau. the use of the biofloc system is also rarely done in kelabau farming. The combination of kelakai leaf silage and biofloc system has the potential to increase the efficiency of kelabau farming by applying environmentally friendly technology. The study aims to analyze the growth performance of kelabau. The research was carried out in the Wet Laboratory located at the Faculty of Fisheries and Marine Science, Lambung Mangkurat University, Banjarbaru City, South Kalimantan Province. The research method used was an experimental approach with a Completely Randomized Design (RAL), consisting of 3 treatments which were repeated 3 times, so that a total of 9 experimental units were obtained, where Treatment K (Control) is commercial feed given at a dose of 5% of biomass weight, Treatment A is kelakai leaf silage at a dose of 5% of biomass weight, and Treatment B is commercial feed + kelakai leaf silage at a dose of 2.5% of biomass weight. The research results showed the best results in relative length of 121.5%, relative weight of 24.0%, and feed utilization efficiency of 47.3%. FCR showed the best results in treatment K of 0.68% and the best survival rate in treatments K and A of 99.3%. Treatment B can be considered as an alternative feed for the cultivation of kelabau in biofloc systems because it can improve growth performance.